LITERATURE OF REVIEW THE INFLUENCE OF ENVIRONMENTAL SATISFACTION, JOB SATISFACTION AND BALANCE OF LIFE AND SALARY ON EMPLOYEE PERFORMANCE AT PT BANK DANAMON INDONESIA TBK - Riyan (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research will explain the influence ofenvironmental satisfaction, job satisfaction andbalance of life and salary on employee performanceusing a literature review. This research found thatthere are 4 hypotheses that need to be answered.This research uses a quantitative design usingnumbers for research decision making. Using SPSSstatistical tools and testing the feasibility of data andmodels and answering hypotheses. This research wasconducted at PT Bank Danamon Indonesia, which isone of the largest banking companies in Indonesia